2018
DOI: 10.3390/nu10111666
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Hemodynamic Effects of Modern Wheat Products Substitution in Diet with Ancient Wheat Products: A Cross-Over, Randomized Clinical Trial

Abstract: Recent evidence suggests that bioactive compounds isolated from cereals and legumes could exert some metabolic and vascular effects in humans. Due to the recent identification of a non-specific lipid transfer protein (nsLTP2) in wheat with antioxidant and anti-inflammatory activity, we aimed to comparatively test the hemodynamic and metabolic effects of ancient wheat foodstuffs (made of organic KAMUT® khorasan wheat) or modern wheat ones, made of a mixture of organic modern commercial durum (T. durum) varietie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Eight weeks of diet based on this heritage cultivar resulted in a significant reduction in total cholesterol, LDL, and glucose [24] in the blood. A decrease in triglycerides and fasting plasma glucose was observed in a randomized, crossover clinical trial on 63 healthy volunteers [81]. Furthermore, a randomized crossover study conducted on 22 patients suffering from acute coronary syndrome confirmed the results, showing again a decrease in blood levels of total cholesterol, LDL-C, fasting glucose, and insulin that were not observed after the consumption of modern cultivars [25].…”
Section: Ancient and Heritage Wheat In Clinical Studysupporting
confidence: 54%
“…Eight weeks of diet based on this heritage cultivar resulted in a significant reduction in total cholesterol, LDL, and glucose [24] in the blood. A decrease in triglycerides and fasting plasma glucose was observed in a randomized, crossover clinical trial on 63 healthy volunteers [81]. Furthermore, a randomized crossover study conducted on 22 patients suffering from acute coronary syndrome confirmed the results, showing again a decrease in blood levels of total cholesterol, LDL-C, fasting glucose, and insulin that were not observed after the consumption of modern cultivars [25].…”
Section: Ancient and Heritage Wheat In Clinical Studysupporting
confidence: 54%
“…Although increased intake of whole grain cereals is seen as protective against CVD [ 1 , 2 ], not all studies consistently show improvement in CVD-related parameters. For example, Cicero et al [ 39 ] using a crossover design and 4 week intervention periods, showed that foodstuffs containing ancient wheat (with high levels of non-specific lipid transfer protein 2 as proposed bioactive) could lower blood pressure, triglycerides and fasting blood levels in pre-hypertensive/borderline high pressure subjects ( n = 63) compared to foodstuffs containing modern wheat varieties low in nsLTP2. Conversely, Vetrani et al [ 40 ] found no effect of whole grain cereal foodstuffs compared to refined grain foodstuffs on glucose homeostasis or plasma lipid parameters in overweight/obese subjects with the metabolic syndrome ( n = 26) after a 12 week intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrient intake was estimated from the 4‐day records before the randomization and at the end of the intervention period. The nutritional evaluation was performed by an expert nutritionist biologist with Software MètaDieta® (Me.Te.Da s.r.l., San Benedetto del Tronto, Italy) using Italian Food Composition databases (Cicero et al, ).…”
Section: Methodsmentioning
confidence: 99%